Picture-based crop monitoring is adopted in India, Ethiopia and Kenya by 6 public and private institutions to advance their agricultural insurance and finance services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Picture-Based Insurance provides affordable high-quality crop insurance by using smartphone images of smallholders’ crops for settlement of claims. PIM research led to large-scale testing and adoption of picture-based crop monitoring by private entities as HDFC ERGO General Insurance (India), Dvara E-Registry (India), the Government of India, ACRE Africa (Kenya), public entity R4 Rural Resilience Initiative (Ethiopia) and the Centre for Agriculture and Bioscience International (CABI) (India, Kenya), creating opportunities to strengthen crop insurance, financing and agro-advisories for millions of farmers.